(untitled) (Research, Society and Development, 2021)
In recent years, Sexually Transmitted Infections (STI) have been increasing worldwide, especially among adolescents. Thus, the study aims to investigate the knowledge that adolescents have about the main signs and symptoms of STIs. This is a cross-sectional, descriptive, interpretative study, with a quantitative approach. The study was carried out in a Public Technical High School in the Northeast of Brazil through an online questionnaire. This analysis consisted of 595 students. The study shows that most students (73,6%) did not know what the main signs and symptoms of STIs were. Women had more information on this subject than men. The article demonstrates that students do not have adequate knowledge about the main signs and symptoms of STIs and this is worrying because they are in the sexual initiation phase.